Love B - Tabanli, Mustafa (New Jersey : Everest Production, 2008)
It is believed to conquer all. It forms the cornerstone of all major religions. It has inspired countless poems, novels, songs, and films. As the 1929 song written by Cole Porter asks, 2What is this thing called love?3 What is earthly love? What is divine or spiritual love? And is it possible that the two can intersect? And how does love impact our physical and mental health? This program explores the physical, emotional and spiritual dimensions of love.
Executive producer, Nasuhi Yurt.
Host : MaryLynn Schiavi.
DVD format
Keywords: Love; Psychology, Religious